The Dopamine Transporter and Cocaine Medication Development: Drug Self-Administration in Nonhuman Primates - Howell, Leonard L.; Wilcox, Kristin M. (The Journal of pharmacology and experimental therapeutics, 2001)
Despite intensive medication development efforts, no effective pharmacotherapy for cocaine abuse has demonstrated efficacy for long-term use. Given the obvious importance of the dopamine transporter in the addictive properties of cocaine, the development and use of compounds that target the dopamine transporter represents a reasonable approach for the pharmacological treatment of cocaine abuse. The therapeutic approach of replacement or substitute agonist medication has been successful, as shown with methadone maintenance for heroin dependence and nicotine replacement for tobacco use. A number of preclinical studies with dopamine transporter inhibitors provide evidence that substitute agonists may be used effectively to reduce cocaine use. Nonhuman primate models of drug self-administration provide a rigorous, systematic approach to characterize medication effectiveness in subjects with a documented history of drug use. Several cocaine analogs and other dopamine transporter inhibitors, including analogs of GBR 12909 and WIN 35,065-2, have been shown to reduce cocaine self-administration in nonhuman primates. A possible limitation to the use of selective dopamine transporter inhibitors as medications is their potential for abuse liability given their demonstrated reinforcing effects in nonhuman primates. However, limited reinforcing properties in the context of treatment programs may be advantageous, contributing to improved patient compliance and enhanced medication effectiveness. Moreover, pharmacokinetic properties that result in slow onset and long duration of action may enhance their effectiveness to reduce cocaine use while limiting their abuse liability.